Taxonomic revision of Brazilian Mactridae Lamarck, 1809 (Bivalvia: Cardiida) - Signorelli, Javier Hernan (2011)
The worldwide distributed family Mactridae Lamarck, 1809, is well represented in the western Atlantic Ocean. An ex-haustive literature research revealed 54 nominal species from the Brazilian coast. The study was done using morphologicalcharacters of shell and in some cases mantle cavity organs. All type material was examined and illustrated. Eleven validliving species are confirmed from the Brazilian littoral and their synonymies and geographic distributions are updated.Redescriptions are provided for Mactrellona alata (Spengler, 1802); Mactrotoma fragilis (Gmelin, 1791); Mulinia clery-ana (d´Orbigny, 1846) and Anatina anatina (Spengler, 1802). The revision of Trinitasia iheringi (Dall, 1897) new combination, reveals the presence of a Tertiary genus among the Recent fauna of South America.